Affective Intensities in Extreme Music Scenes - Overell, R. author. aut Link
XI, 211 p.
Keywords: An ethnographic study of gender, place and belonging, Affective Intensities introduces readers to the embodied sensations, flows and experiences of being in extreme music scenes in Australia and Japan.